Clinical Influence of Mandibular Flexure on Oral Rehabilitation: Narrative Review - Mijiritsky, Eitan; Shacham, Maayan; Meilik, Yuval; Dekel-Steinkeller, Michal (International journal of environmental research and public health, 2022)
Aim: The current paper aims to review mandibular flexure and its clinical implications in the field of oral rehabilitation. Mandibular flexure is a deformity of the mandible, which occurs during jaw movements. Methods and Materials: An electronic database search was conducted using the PRISM model, with a total of 49 articles included. Results: Mandibular flexure affects various stages of oral rehabilitation treatments. Effects of mandibular flexure are more significant in periodontal patients, and in implant-supported restorations, compared to natural teeth, due to differences in the force absorption by the periodontal ligament. Various adjustments must be made to the prosthodontic framework to enable long-term survival of the restorative treatments. Conclusions: Dental practitioners should pay attention to the following: (1) digital impressions are preferred over conventional; (2) mouth opening should be kept to a minimum (as possible, up to 10–20 mm) while also avoiding any anterior movements of the mandible (protrusion); (3) the number of abutment teeth should be kept to a minimum; (4) structures in the lower jaw should be splitted; (5) non-rigid connectors should be used to reduce the effort exerted; (6) in periodontal patients, the preference is for short-span restorations and non-rigid connectors; (7) in implant-supported restorations, it is preferable to divide the framework into two or three segments, utilizing rigid materials with a low elastic modulus. There is no agreement in the literature about the preferred location of the implants in the jaw.